PENYULUHAN NILAI RELIGI DAN NILAI KEARIPAN BUDAYA LOKAL DALAM RANGKA PENGUATAN TATANAN KEHIDUPAN MASYARAKAT - Nandang Rukanda; Tamtam Kamaludin; Cucu Samsudin (IKIP SILIWANGI, 2021)
The Objectives of Community Service These are (1) To know and describe the culture of the people of Padaasih Village, Cisarua District, West Bandung Area in their daily life as a result of their belief in their religion, (2) To find out and describe the culture of the Padaasih Village community in their daily life as an implementation of the local cultural wisdom they hold, (3) This is to determine and describe the impact of the practice of religious beliefs and local cultural wisdom on strengthening the structure of community life in Padaasih Village. The scientific references used in this community service are the concept of counseling, the concept of values, religious values, cultural wisdom, and the meaning of community life. The community service location was carried out in the northern West Bandung area, precisely in Padaasih Village, Cisarua District. The steps taken in this service are (1) Identifying the Problem; through observations and interviews, (2) Literature Study, (3) Compiling Service Design, (4) Treatment of the Community, (5) Conducting Analysis and (6) Writing Service Results Reports. The results of community service show that counseling runs quite effectively and gets a positive response from all components of society. The people of Padaasih Village feel enlightened and have succeeded in adding religious knowledge and increasing awareness of the importance of religious values and local cultural wisdom to be maintained and even applied in everyday life.